Service-dominant logic : premises, perspectives, possibilities - Lusch, Robert F.; Vargo, Stephen L., 1945- (Cambridge : Cambridge University Press, 2014)
In 2004, Robert F. Lusch and Stephen L. Vargo published their groundbreaking article on the evolution of marketing theory and practice toward'service-dominant (S-D) logic', describing the shift from a product-centred view of markets to a service-led model. Now, in this keenly anticipated book, the authors present a thorough primer on the principles and applications of S-D logic. They describe a clear alternative to the dominant worldview of the heavily planned, production-oriented, profit-maximizing firm, presenting a coherent, organizing framework based on ten foundational premises. The foundational premises of S-D logic have much wider implications beyond marketing for the future of the firm, transcending different industries and contexts, and will provide readers with a deeper sense of why the exchange of service is the fundamental basis of all social and economic exchange. This accessible book will appeal to students, as well as to researchers and practitioners.
Contents note continued: Foundational premise 3: goods are distribution mechanisms for service provision -- Foundational premise 4: operant resources are the fundamental source of competitive advantage -- Foundational premise 5: all economies are service economies -- Axiom 2 and foundational premise 6: the customer is always a cocreator of value -- Foundational premise 7: the enterprise cannot deliver value, but can only offer value propositions -- Foundational premise 8: a service-centered view is inherently customer oriented and relational -- Axiom 3 and foundational premise 9: all economic and social actors are resource integrators -- Axiom 4 and foundational premise 10: value is always uniquely and phenomenologically determined by the beneficiary -- Contrasting logics -- Concluding comments -- 4. Service as a guiding framework -- Introduction -- Prior views of services misled -- A more comprehensive view of service -- Implications of'service' thinking.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Customer relations -- Philosophy; Customer services -- Philosophy; Service industries -- Philosophy